Family’s perceptions of their members who use nyaope in Tshwane, South Africa - Doudou K. Nzaumvila; Robert Mash; Toby Helliwell (PLoS ONE, 2025)
Introduction Over the last two decades, nyaope use has evolved to become a prominent substance use disorder in South Africa, posing a significant public health burden. The majority of users are young people who are solely concerned with their next nyaope joint. This study aimed to explore the perception of family members on the factors associated with the use of and dependency on nyaope. Methods This was a descriptive exploratory qualitative study conducted in Tshwane, South Africa. Data were collected from 32 family members of Nyaope users via three focus group interviews conducted by a retired psychologist nurse in the three townships of Tshwane. Results The findings revealed a complex and interconnected web of elements that shape the journey of individuals from the onset of nyaope use to the point of dependence and eventual departure from their family homes. Rather than following a linear path of events, this pathway is characterised by a dynamic interplay of seven distinct themes, namely concealed nyaope use, family concerns and suspicions regarding nyaope use, confirmation of nyaope use, possible reasons for using nyaope, barriers to obtaining assistance for nyaope users, family distress, and the transition from home to a life on the streets. Conclusion Most users ended up being disconnected from their families. Family members’ opinions noted that the problem is perceived to be a web of elements working together rather than a linear path of events. The findings have implications for substance use services, social services, health and police services as well as schools.